As-cast microstructure characteristics of K439B nickel-based superalloy thin- walled castings of different thickness - ZHOU Depeng; SUI Dashan; MA Jinyuan; GUI Daxing; DONG Anping; SUN Baode (Cailiao gongcheng)
K439B is a new type of nickel-based superalloy with a service temperature up to 800 ℃. In the face of the demand for mass reduction of aircraft， the structure of its components is developing in the direction of thin-wall. Thus， it is necessary to study the microstructure of the K439B alloy thin-walled castings. For this purpose， the thin-wall castings with wall thicknesses of 1 mm and 2 mm are designed， and gravity investment casting experiments and numerical simulations are conducted. Comparative analysis of the as-cast microstructure of the castings shows that the growth directions of the dendrites in both 1 mm and 2 mm thin-wall are along the shell wall pointing to the center， the difference is that the growth directions of the dendrites in the 1 mm thin-wall are closer to the vertical angle with the wall. The average primary dendrite arm spacings （PDAS） are 60.64 μm for 1 mm thin-wall and 46.23 μm for 2 mm thin-wall， respectively. The average secondary dendrite arm spacings （SDAS） are 19.31 μm for 1 mm thin-wall and 22.69 μm for 2 mm thin-wall， separately. Meanwhile， the average grain size of the 1 mm thin-wall is 216.61 μm， and the corresponding size of the 2 mm thin-wall is 239.11 μm. Combined with numerical simulation analysis， it is shown that the relationship trend between dendrite arm spacings， temperature gradient， and cooling rate basically matches the existing empirical formula， but the relationship between PDAS and temperature gradient and cooling rate no longer simply matches the formula when the wall thickness is reduced to a certain critical thickness. These results of the experimental and simulation analysis could provide a reference to rationally design the casting process for the K439B nickel-based superalloy thin-walled casting crafts.